Techno security's guide to e-discovery and digital forensics - Wiles, Jack. (Burlington, MA : Syngress Pub., 2007)
This book provides IT security professionals with the information (hardware, software, and procedural requirements) needed to create, manage and sustain a digital forensics lab and investigative team that can accurately and effectively analyze forensic data and recover digital evidence, while preserving the integrity of the electronic evidence for discovery and trial. IDC estimates that the U.S. market for computer forensics will be grow from $252 million in 2004 to $630 million by 2009. Business is strong outside the United States, as well. By 2011, the estimated international market will be $1.8 billion dollars. The Techno Forensics Conference, to which this book is linked, has increased in size by almost 50% in its second year; another example of the rapid growth in the digital forensics world. The TechnoSecurity Guide to Digital Forensics and E-Discovery features: * Internationally known experts in computer forensics share their years of experience at the forefront of digital forensics * Bonus chapters on how to build your own Forensics Lab * 50% discount to the upcoming Techno Forensics conference for everyone who purchases a book.
Introduction; Authentication; Email Forensics -- Developing an Enterprise Digital Investigative/Electronic Discovery Capability; Advanced Training For Your Electronic Discovery Team; Digital Forensics in a Multi Operating System Environment; Digital Forensic Investigation Operations; Working Together To Build a Regional Forensics Lab; Forensic Examinations in a Terabyte World; Starting a Career In The Field of Techno Forensics -- Degrees, Certifications and Networking; Standards in Digital Forensics; Selecting The Hardware For Your Forensics Computer; Death By a Thousand Cuts; Balancing Records & Information; Management through Electronic Discovery; Win or Lose -- You Choose! -- Inside Secrets to Presenting The Best You; Mac Forensics.
"The Training Co."
Includes index.
Keywords: Computer crimes -- Investigation; Computer networks -- Security measures; Computer security; Electronic books